Aggressive Pseudomyxoma Peritonei: A Case Report with an Unusual Clinical Presentation. (13th November 2013) - Touloumis, Zisis; Galyfos, George; Kavouras, Nikolaos; Menis, Michalis; Lavant, Laurant
Abstract : Introduction . Pseudomyxoma peritonei (PMP) is an uncommon surgical entity. We report a case of aggressive disease with an unusual clinical presentation and we analyze current data on diagnosis and management of PMP. Case Presentation . A 71-year-old male patient presented with intermittent diarrhea and loss of appetite during the last two months, without any other classic symptoms of PMP. The clinical examination was misleading due to patient's obesity. The radiological evaluation revealed ascites of the abdomen and possible mucocele of the appendix, whereas the laboratory exams showed high values of specific tumour markers. The patient underwent an exploratory laparotomy for definite diagnosis. Biopsies and immunohistochemical examination confirmed the diagnosis of an aggressive and extended peritoneal mucinous carcinomatosis (PMCA). The patient was programmed for adjuvant systematic chemotherapy, which was not completed due to progression of the disease. Conclusions . Progressed PMP can present with unspecific symptoms that mislead diagnosis. Cytoreductive surgery in combination with systematic chemotherapy could be appropriate for aggressive PMCA, even with an unfavourable prognosis.